FRI0173 Gastrointestinal perforations with certolizumab PEGOL. (23rd January 2014) - Fleischmann, R.; Rubbert-Roth, A.; Combe, B.; VanLunen, B.; Andrews, P.; de Longueville, M.
Abstract : Background: Gastrointestinal (GI) perforations have emerged as an uncommon but potentially serious safety concern for patients with rheumatoid arthritis (RA). 1 It is thought that treatment with some biologics (particularly those targeting the IL-6 pathway) may increase the risk of GI perforation in RA patients. 2 Certolizumab Pegol (CZP) is an anti-TNF registered in RA. Objectives: To assess the rate of GI perforations occurring in CZP-treated RA patients for a total of >8500 patient years (PY). Methods: A pooled safety analysis was performed for 7 randomized controlled trials (RCTs) of CZP in RA and their open-label extensions (OLEs). RCTs included RAPID 1, RAPID 2, FAST4WARD and REALISTIC. Pooling was performed across all CZP doses. GI perforations were defined according to the preferred terms "gastrointestinal perforation" and "diverticular perforation". Cases were recorded by the clinical investigator. Results: As of 31st October 2010, 3397 RA patients had been treated with CZP in all studies (RCTs plus OLEs) for a total of 8658 PY. The pooled safety analysis revealed that 1 GI perforation (0.01 events/100 PY) and 1 diverticular perforation (0.01 events/100 PY) occurred in all studies. No cases occurred during the RCTs. The first case of GI perforation occurred in a 64 year old female treated with CZP 200 mg Q2W for 9 months, MTX, diclofenac and oral corticosteroids. The patient was hospitalized for a peritonitis related to colonic perforation, which was successfully treated by surgery. The second case, a diverticular perforation, occurred in a 61 year old male treated with CZP 400 mg Q4W for 2.6 years, MTX and oral corticosteroids. The patient was hospitalized for peritonitis due to perforated diverticulitis of the sigmoid colon and was successfully treated by sigmoid resection. Conclusions: No safety signal exists for an increased risk of GI perforations associated with the use of CZP. References: Curtis JR et al. Arthritis & Rheumatism 2011;63:346-351. Schiff et al. Arthritis Research & Therapy 2011;13:R141. Disclosure of Interest: R. Fleischmann Grant/Research support from: UCB Pharma, Consultant for: UCB Pharma, A. Rubbert-Roth Consultant for: UCB Pharma, Speakers Bureau: UCB Pharma, B. Combe Grant/Research support from: UCB Pharma, Consultant for: UCB Pharma, B. VanLunen Employee of: UCB Pharma, P. Andrews Employee of: UCB Pharma, M. de Longueville Employee of: UCB Pharma